Evaluating the significance of external funding in underdeveloped rural areas of Zimbabwe. A case of Mbire RDC. - Siyavizva, Kudzai P. (Midlands State University, 2017)
The study evaluated the impact of external funding in Mbire RDC through the assessment of the projects that are being implemented. The thrust of this project is premised on the fact that despite the presence of donor agencies Mbire RDC remains one of the most underdeveloped and impoverished district in the country. Donor funding has proved to be insignificant since the local communities continue to perform dismal in every aspect of their lives. The socio-economic livelihoods of the society remain miserable whilst there are over seventeen non-governmental organizations operating in the district. The study embarked on scholarly review and perspectives concerning external funding and underdevelopment. The study findings highlighted that total positive transformation will never take place since there are numerous factors militating against development. These challenges were investigated through interviewing the government departments, the local authorities, the non-governmental organizations operating in the district, questionnaires to the community, observations and documentary reviews. It utilized both qualitative and quantitative approaches. The major findings was that there is too much political interference, the prevalence of corruptive tendencies, stifled internal policies, the public attitude, high dependency syndrome and lastly but not least lack of sustainability. The study noted that exclusion of some structures in a rural set up compromises citizenry participation. The study regarded these factors as major impediments to the continuity and viability of externally funded projects. Finally, the research made conclusions and recommendations, one of the recommendations being that there is need to regard the community as the stakeholders in planning and management of projects rather than beneficiaries which creates a sense of ownership.